Modelling and Simulation for Autonomous Systems c - Mazal, Jan.; Fagiolini, Adriano; Vasik, Petr.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
This book constitutes the thoroughly refereed post-workshop proceedings of the 6th International Workshop on Modelling and Simulation for Autonomous Systems, MESAS 2019, held in Palermo, Italy, in October 2019. The 22 full papers and 13 short papers included in the volume were carefully reviewed and selected from 53 submissions. They are organized in the following topical sections: M&S of intelligent systems - AI, R&D and application; future challenges of advanced M&S technology; AxS in context of future warfare and security environment (concepts, applications, training, interoperability, etc.).
M&S of Intelligent Systems - AI, R&D and Application -- Future Challenges of Advanced M&S Technology -- AxS in Context of Future Warfare and Security Environment (Concepts, Applications, Training, Interoperability, etc.).
Keywords: Computer simulation; Artificial intelligence; 9; Computers, Special purpose; Computer Modelling; Artificial Intelligence; Computer Communication Networks; Special Purpose and Application-Based Systems